The effects of school quality in the origin on the payoff to schooling for immigrants - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2010)
The payoff to schooling among the foreign born in the US is only around one-half of the payoff for the native born. This paper examines whether this differential is related to the quality of the schooling immigrants acquired abroad. The paper uses the Over-education/ Required education/Under-education specification of the earnings equation to explore the transmission mechanism for the origin-country school quality effects. It also assesses the empirical merits of two alternative measures of the quality of schooling undertaken abroad. The results suggest that a higher quality of schooling acquired abroad is associated with a higher payoff to schooling among immigrants in the US labor market. This higher payoff is associated with a higher payoff to correctly matched schooling in the US, and a greater (in absolute value) penalty associated with years of under-education. A set of predictions is presented to assess the relative importance of these channels, and the over-education channel is shown to be the more influential factor. This channel is linked to greater positive selection in migration among those from countries with better quality school. In other words, it is the impact of origin country school quality on the immigrant selection process, rather than the quality of immigrants' schooling per se, that is the major driver of the lower payoff to schooling among immigrants in the US.
Keywords: I21; J24; J31; J61; F22; 330; immigrants; schooling; school quality; earnings; selectivity; Bildungsertrag; Migranten; Einwanderung; USA; Bildungsniveau; Allgemeinbildende Schule; Dienstleistungsqualität; Auswanderung; Welt